Thieno[2,3-b]pyridine derivatives: a new class of antiviral drugs against Mayaro virus - Amorim, Raquel (2017)
Mayaro virus (MAYV) is an arthropod-borne virus and a member of the family Togaviridae, genus Alphavirus. Its infection leads to an acute illness accompanied by long-lasting arthralgia. To date, there are no antiviral drugs or vaccines against infection with MAYV and resources for the prevention or treatment of other alphaviruses are very limited. MAYV has served as a model to study the antiviral potential of several substances on alphavirus replication. In this work we evaluated the antiviral effect of seven new derivatives of thieno[2,3-b]pyridine against MAYV replication in a mammalian cell line. All derivatives were able to reduce viral production effectively at concentrations that were non-toxic for Vero cells. Molecular modeling assays predicted low toxicity risk and good oral bioavailability of the substances in humans. One of the molecules, selected for further study, demonstrated a strong anti-MAYV effect at early stages of replication, as it protected pre-treated cells and also during the late stages, affecting virus morphogenesis. This study is the first to demonstrate the antiviral effect of thienopyridine derivatives on MAYV replication in vitro, suggesting the potential application of these substances as antiviral molecules against alphaviruses. Additional in vivo research will be needed to expand the putative therapeutic applications.